Taking disputes online in a pandemic-stricken world: Do we necessarily lose more than we gain? - QUEK ANDERSON, Dorcas (Institutional Knowledge at Singapore Management University, 2020)
Online dispute resolution (ODR) used to be a secondary feature of the courts, arbitration institutions and mediation providers. ODR systems involving problem diagnosis, facilitation and online adjudication were primarily utilised for low value claims and not extended to all legal claims. Private mediation was largely conducted only on online platforms to bridge physical distances. However, the COVID pandemic has very abruptly compelled the courts and other dispute resolution practitioners to shift face-to-face processes to the virtual environment. ODR is likely to be the mainstream, and no longer the alternative, way of managing disputes in the immediate future. The rapid migration of dispute resolution to the online sphere has given the dispute resolution field little time to thoughtfully consider the impact of different communication modes on substantive and procedural justice. This short article discusses the gains and losses brought about by this seismic shift for adjudicatory processes in courts and arbitration, and more consensual processes such as mediation. It draws upon the latest social science and dispute resolution research to examine how virtual modes of communication potentially impinge on perceptions of fairness, rapport-building, open justice, accurate assessment of demeanour and power imbalances. It also underscores the unique opportunities given by the online environment to advance procedural and substantive justice in creative ways. A considered analysis of these issues will ultimately enable the dispute resolution landscape to reap more gains than losses in the post-pandemic world.